The study case of public perception toward service quality render by Marudi District Council / Abdul Kadir Said Malim - Said Malim, Abdul Kadir (2008)
The purpose of this paper is to identify the level of satisfaction and dissatisfaction of service quality perceived by public whilst doing business at Marudi District Council. Local councils in Malaysia have been given wide powers within the Local Government Act of 1976. The mandatory functions include all critical functions such as refuse collection, street lighting, activities pertaining to public health, providing amenities, recreational parks, housing and commercial activities. The main objective ofthe organization is to achieve higher productivity in term of profit or quality. To achieve this objective, the employees have an importance role to ensure that their organization is active and productive. Service quality is a concept that has implication for the input features of a service that relate to fiscal, human and material, as well as to differences in its frequency, convenience, timeless and scope.